OVERVIEW OF THE LEVEL OF COMMUNITY KNOWLEDGE ABOUT FLOOD DISASTER MITIGATION IN VILLAGE X - Dwi Putri, Berlian Widyanty; Muthmainnah (Indonesian Journal of Community Health Nursing, 2024)
Introduction: Flooding is a condition where an area or plain is submerged by water due to an increase in the volume of water. Flood disaster cause various physical and mental health impacts and even property losses. This flood can be prevented by the community through flood disaster mitigation. Flood mitigation needs to be developed and improved through appropriate and efficient measures. This research has to describe the level of public knowledge about flood disaster mitigation in village x. Method: This research uses a descriptive research method, with a cross-sectional research design and a quantitative approach. The sample in this study was 86 respondents with a random sampling technique. The analysis used in this research is univariate analysis. Results: the result of the study indicate that respondents 75,6% have a good level of knowledge. Because the community has enough to understand the importance of the surrounding environment, public knowledge of flood disaster mitigation is good because many people obtain information about flood disaster mitigation in media mass and electronic. Conclusion: the community has a good level of knowledge, and it is recommended to be able to increase knowledge about flood disaster mitigation.